Water Charge and Conservation of Natural Areas: An Ex‐Ante Assessment of a Policy Proposal for the Mantiqueira Region, Brazil - Ademir Rocha; Eduardo Haddad; Alan Leal; João Corrêa (Water Resources Research, 2023)
Abstract Water plays a central role in several socioeconomic and environmental nexuses. Faced with various anthropogenic pressures that act as water scarcity drivers and knowing that the unavailability of water can be a limiting factor for economic development, there is an urgent need for the design and evaluation of economic instruments that help in the management of water resources. This article presents a proposal and assessment for a Pigouvian water charge instrument. The instrument suggests imposing a charge based on the amount of water consumed, targeting the agriculture, livestock, forest extraction, and aquaculture sectors. The revenue generated from this charge could be utilized to fund reforestation initiatives and support government expenditures, thereby creating both environmental and economic advantages. Based on a calibrated static computable general equilibrium economic model for the Brazilian Mantiqueira region, it was possible to estimate that a water charge policy at a rate of R$ 0.10/m3 (US$ 0.026/m3) could lead to an increase in the Brazilian GDP in the benchmark year by US$ 10.7 million. Economic benefits could also be verified at the regional level, especially in those areas where there are water‐intensive economic activities. On the environmental side, the water charge could incentivize actions capable of recovering approximately 80 km2 of natural areas.